Constrained synthesis of the Linear Antenna Array using Social Group Optimization - Rahiman Sheik, Abdul; Kalva Sri Rama Krishna, Dr (International Journal of Engineering and Technology, 2018)
In this paper, novel algorithm known as social group optimization is use for array synthesis problem. The algorithm is implemented to the electromagnetic problem solving and its performance is evaluated. The array design is carried out with the objective of sidelobe level (SLL) suppression with uniform beam width (BW) constraint. The amplitude only technique is used to determine the coefficients of current excitation which produce the desired radiation pattern with the objectives and constraints. The analysis is carried out in terms of radiation pattern for different length of linear arrays. The simulation based experimentation is carried out in Matlab.Â Â